Introduction: Special Issue on Teaching Academic Writing in Canada - Seeley, Sarah; Tekin, Oguzhan; Evans-Tokaryk, Tyler (Discourse and Writing/Rédactologie, 2024)
This article introduces a Special Issue of Discourse and Writing/Rédactologie: Teaching Academic Writing in Canada. It contextualizes the research and pedagogical discussions contained herein, and it underlines how these contributions emphasize two major trends on the Canadian landscape of academic writing: the movement toward decolonizing academic writing and diverse approaches to writing in the disciplines and writing centre practices.